A Socio-legal Perspective on the Restrictions and Restrictive Interpretation of Fundamental Rights in Sri Lanka - Thilakarathna, K.A.A.N. (University of Jaffna, 2018)
The disclosure on fundamental rights from a socio-legal point of view has been a somewhat recent development. According to this school of thought rights are seen as a friction that exist among the members of a society where they are constantly making claims to enhance their respective rights. Socio-legal perspective looks at the sociological factors, such as gender, religion, economic status, culture, ethnography and the social interactions of the parties in general when they live in a communi-ty and how these interactions represents the virtues and values of a community. The Sri Lankan ex-perience has shown that with its developments of the Constitutional Jurisprudence ‘Fundamental rights’ plays a very important role in the develop-ment of a society. For a long time, that is to say till 1978 none of the Sri Lankans enjoyed justiciable fundamental rights. Even the justiciable rights granted under the 1978 constitution was hampered severely with the restrictions and the restrictive in-terpretations that were given to them. The constitu-tion and the judiciary has therefore, acted as a barrier at times against the wishes of society. How-ever, these barriers that have been so created has at times urged the legislature and especially the judiciary to take a more liberal viewpoint with re-gard to these fundamental rights when people have tried to vindicate them. From a socio-legal back-ground we can see that both the law shapes society and vice versa. Still due to the differences that exist among the institutions and those who are re-sponsible for interpreting the law, people have been unable to enjoy the fundamental rights guaranteed under the constitution to the fullest. There for it is suggested that when implementing restrictions up-on fundamental rights granted under a constitu-tion, a through consultation must be made with the members of the society and then after one should decide on the scope and the ambit of the re-strictions which are going to be placed upon the fundamental rights. Therefore, it becomes very important to look at the matter from a sociological perspective.
Keywords: Fundamental rights; Interpretation; Law; roportionality; Sociology